New holographic scheme for multiplex image storage in photorefractive crystals - Priadko, Larysa; Bugaychuk, S.; Galich, G.; Gnatovsky, Olexandr; Medved, Nataliya (My University, 2000)
The new holographic scheme with a photorefractive crystal, which is based on the interference of two identical object beams, are studied for the purpose of multiplex image storage. It is shown, that every image recorded by the proposed method possesses a property of associative readout. The proposed scheme can be applied in optical implementation of associative network, all-optical associative memory, template matching, optical interconnection. Розглянута нова голографічна схема з фоторефрактивними кристалами, яка заснована на інтерференції двох однакових предметних пучків, з метою багаторазового запису зображення. Показано, що кожне зображення, записане за допомогою запропонованого методу, має властивість асоціативного зчитування. Запропонована схема може бути застосована для реалізації оптичної асоціативної мережі, оптичної асоціативної пам'яті, в оптичних з'єднаннях.
Keywords: hologram; correlator; photorefractive crystals; голограма; фоторефрактивні кристали; корелятор; кафедра фізики та професійної безпеки